Phytochemical and Morphophysiological Responses in Basil (Ocimum basilicum L.) Plant to Application of Polyamines - E Danaee; V Abdossi (Institue of Medicinal Plants, ACECR, 2019)
Background: The application of polyamines as a plant growth substance with effect on a wide range of plant growth and development processes include cell division, flowering, senescence delay, membrane stability, absorb active radicals and different stress tolerance and polyamines Function as a anti-senescence and anti-stress agents in the plant and on the other hand the competitiveness of their production with ethylene can be effected directly or indirectly on growth factors and the plantchr('39')s metabolic. Objective: This study was directed to investigate the effect of foliar spraying of polyamines on morpho-physiological and phytochemical traits of Basil. Methods: This experiment were done as a randomized complete design with 10 treatments included spermine, spermidine and putresin in 3 level 50, 100 and 150 ppm in 3 replication. Pot without foliar spraying of polyamines Used as a control. Results: The results showed spraying with different levels of spermine, spermidine and putresin had a significant effect(P≤ 0.01) on shoot and root fresh weight, shoot and root dry weight and amount of essential oil and also significant effect(P≤ 0.05)on leaf total chlorophyll and vitamin C. Application spermidine 100ppm increased traits such as shoot and root fresh weight, shoot and root dry weight and amount of essential oil than control and putresin 100 ppm improved traits such as leaf total chlorophyll and vitamin C. Conclusion: Phytochemical and Morphophysiological traits in Basil (Ocimum basilicum L.) plant increased with foliar spraying of different level of spermine, spermidine and putresin. As, spraying with spermidine and putresin 100 ppm improved all attributes traits compared to the control.